Protein dynamics and conformational changes explored by hydrogen/deuterium exchange mass spectrometry. (October 2019) - Zheng, Jie; Strutzenberg, Timothy; Pascal, Bruce D; Griffin, Patrick R
Highlights: Introductory bases and equations of HDX-MS. Protein dynamics explored by HDX-MS. Representative case studies that measured by HDX-MS. Future directions of HDX-MS. Abstract : Proteins are not rigid bodies under their physiological conditions. Here we discuss a solution-phase structural proteomics technique, hydrogen deuterium exchange coupled with mass spectrometry (HDX-MS), as a means to study protein dynamics, which can complement other structural approaches. We outline the background theory and highlight the utility of HDX-MS measurements in two case studies involving a nuclear receptor and an innate immunity receptor. We also discuss emerging software advances for improving data analysis and three-dimensional visualization.